2013
DOI: 10.1007/s10142-013-0310-y
|View full text |Cite
|
Sign up to set email alerts
|

A root-specific wall-associated kinase gene, HvWAK1, regulates root growth and is highly divergent in barley and other cereals

Abstract: Wall-associated receptor-like kinases (WAKs) are important candidates for directly linking the extracellular matrix with intracellular compartments and are involved in developmental processes and stress response. WAK gene family has been identified in plants such as Arabidopsis and rice. Here, we present a detailed analysis of the WAK1 gene from barley cv. Golden Promise, mapped to chromosome 5H. Three BAC clones corresponding to the WAK fragment were sequenced and the full-length WAK1 gene was characterized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Indeed, expression of WAK1 in Arabidopsis was found to be induced by aluminum treatment (Sivaguru et al, 2003), and WAKL4 is related to mineral nutrition responses (Hou et al, 2005). Wall-associated kinases are necessary for normal cell enlargement (Cosgrove, 2001;Wagner and Kohorn, 2001), and in barley and rice, WAK genes were found to affect root growth Gupta, 2008, 2011;Kaur et al, 2013). Our results indicate that multiple SNPs within Sb03g006765 are consistently associated with sorghum performance under low P in the two association panels.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Indeed, expression of WAK1 in Arabidopsis was found to be induced by aluminum treatment (Sivaguru et al, 2003), and WAKL4 is related to mineral nutrition responses (Hou et al, 2005). Wall-associated kinases are necessary for normal cell enlargement (Cosgrove, 2001;Wagner and Kohorn, 2001), and in barley and rice, WAK genes were found to affect root growth Gupta, 2008, 2011;Kaur et al, 2013). Our results indicate that multiple SNPs within Sb03g006765 are consistently associated with sorghum performance under low P in the two association panels.…”
Section: Discussionmentioning
confidence: 69%
“…These features are typical of cytoplasmic Ser/Thr wall-associated kinase (WAK) proteins, which span the plasma membrane and extend to the extracellular region to bind tightly to the cell wall (He et al, 1999). According to our sequence data, all selected sorghum SbPSTOL1 genes possess three exons and two introns, which is the typical intron-exon organization of Arabidopsis (He et al, 1999;Kanneganti and Gupta, 2008), barley (Hordeum vulgare; Kaur et al, 2013), and rice (Zhang et al, 2005) WAKs. In addition, five highly similar WAK genes were found to lie in a 30-kb cluster in Arabidopsis (He et al, 1999), which resembles the genome organization of the SbPSTOL1 genes at position 60 Mb on chromosome 3.…”
Section: Discussionmentioning
confidence: 76%
“…Wall-associated kinases have been found to play a role in disease resistance (30,31), phosphorus-starvation tolerance (32), and developmental processes such as root growth (33) and gametophyte development (34). A recent study reported that the maize quantitative head smut resistance gene qHSR1 also encodes a wall-associated kinase.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in rice > 100 members were found (Zhang et al ., ; Kanneganti & Gupta, ). A number of WAK genes in monocots have been shown to be associated to several functional aspects, such as biotic diseases (Li et al ., ; Hurni et al ., ; Zuo et al ., ; Shi et al ., ; Hu et al ., ), tolerance to phosphorus deficiency (Hufnagel et al ., ), root growth (Kaur et al ., ), as well as gametophyte development (Wang et al ., ). WAKs are the only known proteins that physically link the cell wall to the plasma membrane (Brutus et al ., ; Kohorn & Kohorn, ).…”
Section: Discussionmentioning
confidence: 99%